Degeneration-Dependent Retinal Remodeling: Looking for the Molecular Trigger - Telias, Michael; Nawy, Scott; Kramer, Richard H. (Frontiers in Neuroscience, 2020)
Vision impairment and blindness in humans are most frequently caused by the degeneration and loss of photoreceptor cells in the outer retina, as is the case for age-related macular degeneration, retinitis pigmentosa, retinal detachment and many other diseases. While inner retinal neurons survive degeneration, they undergo fundamental pathophysiological changes, collectively known as ‘remodeling’. Inner retinal remodeling downstream to photoreceptor death occurs across mammalian retinas from mice to humans, independently of the cause of degeneration. It results in pervasive spontaneous hyperactivity and membrane hyperpermeability in retinal ganglion cells, which funnel all retinal signals to the brain. Remodeling reduces light detection in vision-impaired patients and precludes meaningful vision restoration in blind individuals. In this review, we summarize current hypotheses proposed to explain remodeling and their potential medical significance highlighting the important role played by retinoic acid and its receptor.